Comparison Between Veress Needle (Closed)Technique and Open Technique in Laparoscopic Cholecystectomy - Tariq Nawaz, Muhammad Waqas Ayub, Amjad Umair, Atif Khan, Qasim Ali , Faisal Murad, Idrees Anwar (Journal of Rawalpindi Medical College, 2016)
Background: The aim of this study is to compare open cholecystectomy with needle (closed) technique in laparoscopic cholecystectomy in terms of outcomes and complications. Methods : In this comparative study patients undergoing cholecystectomy were randomized to be in either of the two groups. Each containing 70 patients. Inclusion criteria was, patients with age 20 to 50 years with symptomatic gall stones disease, and without any other general contraindication for laparoscopic surgery . All patients were diagnosed by history ultrasound abdomen. All patients having contraindications to laparoscopic procedure like respiratory compromise, malignancy or any other comorbidities were excluded from the study.Group A constituted 70 patients and all those were randomized for open technique while group B also contained the same number of patients and they were randomized for Veress needle technique. Open technique was performed through skin incision and then dissecting the fascia for gaining access to abdomen by inserting trocar while the closed technique involves direct insertion of Veress needle into abdominal cavity for pneumoperitoneum creation and then trocar placement. The parameters compared were access time , gas leak, visceral injury, vascular injury, need for conversion, umbilical port site hematoma, umbilical port site infection, umbilical port site hernia. Patients were assessed after discharge at the first post operative day, seventh day then after 2 months, 6 months, and after 1 year and last visit on 18 months for assessment of complications. Results: Out of 140 patients, 90 were females and 50 patients were males. Age ranged from 22 to 55 years with mean age of 40 years. The mean time needed to create pneumoperitoneum was 4±1 minutes in veress needle technique and 5±1 in open method (p-value = 0.000) . Gas leak was observed in 15 patients in group A where as no patient had a gas leak in group B (p-value=0.000). Pneumoperitoneum was achieved in all 150 cases. There was one case of visceral injury in which ileal mesentery was damaged while inserting trocar (p-value = 0.316). It was managed laparoscopically. No vascular injury was noted in both groups. Neither open nor closed techniques were associated with conversion to open cholecystectomy regarding access to peritoneal cavity. Two (1,3%) patients had post operative hematoma at the umbilical port site in group A whereas no one developed this complication in group B (p-value = 0.154) . Four (2.6 %) patients presented with surgical site infection at the umbilical trocar site(p-value=0.042). No complications were noted in the veress needle technique. No patient presented with umbilical port site hernia after 18 months of follow up. Conclusion: Both the open and closed method for gaining access into peritoneal cavity are safe but the veress needle method has advantage of less time taken to enter into the abdominal cavity as compared to open method and port site complications like port site hematoma formation and infection are more in open technique.